(untitled) (Tanzania Medical Journal, 2024)
Background Dengue is classified as among Neglected Tropical Diseases (NTD) in Tanzania. Dengue and Malaria are mosquito-borne diseases, however, unlike Malaria, Dengue is neither programmatically integrated into the Malaria program nor in any other vertical program. However, the World Health Organization (WHO) recommends that Dengue control to be part of Integrated Vector Management (IVM). Study objective To explore organizational facilitators and barriers to the integration of dengue into the National Malaria Control Program (NMCP) in Tanzania. Materials and Methods A cross-sectional exploratory study design was conducted between July and August 2020 whereby 15 key informants from the Ministry of Health, Community Development, Gender, Elderly, and Children (MoHCDGEC), National Malaria Control Program (NMCP), and NTD program were involved. An inductive thematic analysis approach was applied to analyze the gathered data where themes, codes, and categories were determined by the data collected. Results Readiness of the available human resources to support the integration, the existence of a defined organizational structure, the existence of policy and guidelines for integration, the availability of funds for integration, and stakeholders’ interests; were found to be organizational facilitators for the integration of dengue into NMCP in Tanzania. The political will of the government forms an integral part of the enabling factors for organizational factors for dengue integration into malaria programs. However, additional costs, varying donor interests, and additional workload were found as organizational barriers to the integration of dengue into the NMCP. Conclusion The facilitators and barriers revealed by this study on the integration of dengue control to the NMCP act as an eye-opener toward the integration of dengue into IVM. Concerted efforts are therefore advocated toward the implementation of IVM with dengue integrated. Moreover, large-scale study can be conducted on the mechanisms and best approaches of integration of dengue into malaria programs.